Analisis UU Nomor 19 Tahun 2016 tentang Jual Beli Berbasis Informatika dan Transaksi Elektronik Menurut Pandangan Syariah Islam - Akrim Billah (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2019)
ABSTRACT 2018 is the year in which the digital world is increasingly sophisticated, digital developments in the millennial era make the world in one grip, especially in the world of online buying and selling. From internal and external cities can easily interact through electronic media. With the development of information technology that has caused world relations to be unlimited and cause rapid economic changes, buying and selling transactions can also be carried out through electronic transactions that are not limited by time and place. Islam is a religion that regulates everything in human life, in Islamic sharia, there are rules related to buying and selling. Islam has previously expanded its principle interpretation and norms in material matters that are intangible. As the world changes into globalization, the accelerated process of development from various aspects cannot be stopped, especially the world of Online Buying and Selling, so that the basic rules and norms emerge overall intangible material issues established in Indonesia in the Information and Electronic Transactions Act. The purpose of this study is to explain how the Islamic Sharia views about the practice of buying and selling and also how the practice of buying and selling based on Information and Electronic Transactions according to Law No. 19 of 2016. The conclusion of this study is that informatics-based buying and selling and electronic transactions as regulated in Islam and Law No. 19 of 2016 are valid as long as they fulfill the requirements in the sale and purchase, and give good faith as stipulated in the Act. Keywords: Law, buying and selling, Islamic sharia